A molecular dynamics study on the thermal rectification effect at the solid–liquid interfaces between the face-centred cubic (FCC) of gold (Au) with the surfaces of (100), (110) and (111) crystal planes facing the liquid methane (CH4). Issue 1 (2nd January 2019) - Saleman, Abdul Rafeq bin; Chilukoti, Hari Krishna; Kikugawa, Gota; Ohara, Taku
ABSTRACT: A molecular dynamics study on the solid–liquid (S-L) interfaces for solid wall of gold having the face-centred cubic of (100), (110) and (111) crystal planes contacting liquid methane was examined using non-equilibrium molecular dynamics simulations. An investigation on the thermal rectification effect was performed by measuring the thermal boundary conductance (TBC) at the S-L interface. Thermal rectification can be defined as the differences in the TBC at the interface between the two opposite heat flow directions; one is from the liquid to solid and vice versa. The thermal rectifications are up to 13% for (110) crystal plane, followed by 6% and 0.3% for (111) and (100) crystal planes, respectively. It was found that the TBC at the S-L interface was influenced by the magnitude of the adsorption of liquid molecules at the vicinity of the interface. The results show that due to the different temperature distribution, different magnitude of the adsorption of liquid molecules is generated for the two opposite heat flow directions. On the surface of the solid walls for (110) crystal plane, where lattice-scale corrugation exists, it was found that there exists difference in distance between the surface layers of the solid and liquid across the interface between the cases of the two opposite heat flow directions, which affects the TBC at the interface. The present results suggest that the factors that influence the thermal rectification at the S-L interface are the magnitude of the adsorption of liquid molecules and the surface structure of the solid walls that differ significantly among the three types of crystal planes.